Study of double parton scattering in photon + 3 jets final state : in proton-proton collisions at √s = 7TeV with the CMS experiment at the LHC.: in proton-proton collisions at √s = 7TeV with the CMS experiment at the LHC. (2017) - Chang, You-Hao
No abstract available